The Effect of Quality Of Work Life on Employee Performance Through Job Satisfaction at the Bantaeng MSME Cooperative and Trade Office - Hakim, Maksud; Manippi, Wahyu Anugrah (International Conference On Association Of Indonesian Entrepreneurship Study Programs, 2024)
This study aims to analyze the influence of quality of work life  on performance through employee job satisfaction, both directly and indirectly. The method of this research is quantitative. This research was conducted on employees at the Bantaeng MSME Cooperative and Trade Office as many as 100 respondents using the purposive sampling technique. The data collected by questionnaire was then analyzed by the Path  Analysis method using the SPSS 23 application. While the hypothesis test uses the t-test and to test the direct and indirect influence  of the quality of work life variable, on performance through job satisfaction using the sobel test. From the results of the study, conclusions were drawn. (1)There is a positive and significant influence between the quality of work life variable on job satisfaction at the Bantaeng MSME Cooperative and Trade Office. (2)There is a positive and significant influence between the quality of work life  variable on employee performance at the Bantaeng MSME Cooperative and Trade Office. (3)There is a positive and significant influence between job satisfaction variables on employee performance at the Bantaeng MSME Cooperative and Trade Office. (4) For the indirect influence, the variable quality of work life  on employee performance through job satisfaction at the Bantaeng MSME Cooperative and Trade Office "is accepted